Increased levels of plasma nucleotides in patients with rheumatoid arthritis. (31st August 2020) - Kishikawa, Toshihiro; Maeda, Yuichi; Nii, Takuro; Arase, Noriko; Hirata, Jun; Suzuki, Ken; Yamamoto, Kenichi; Masuda, Tatsuo; Ogawa, Kotaro; Tsuji, Shigeyoshi; Matsushita, Masato; Matsuoka, Hidetoshi; et al.
Abstract: Novel biomarkers of rheumatoid arthritis (RA), in addition to antibodies against cyclic citrullinated peptides, are required. Metabolome analysis is a promising approach to identify metabolite biomarkers for clinical diagnosis. We adopted a comprehensive non-targeted metabolomics approach combining capillary electrophoresis time-of-flight mass spectrometry (TOFMS) and liquid chromatography TOFMS. We constructed metabolomics profiling of 286 plasma samples of a Japanese population [92 RA patients, 13 systemic lupus erythematosus (SLE) patients and 181 healthy controls). RA case–control association tests showed that seven metabolites exhibited significantly increased levels in RA samples compared with controls ( P < 1.0 × 10 −4 ; UTP, ethanolamine phosphate, ATP, GDP, ADP, 6-aminohexanoic acid and taurine), whereas one exhibited a decreased level (xanthine). The plasma levels of these eight metabolites were not significantly different between seropositive and seronegative RA patients ( P > 0.05; n = 68 and 24, respectively). The four nucleotide levels (UTP, ATP, GDP and ADP) were significantly higher in the non-treatment patients in comparison between patients with and without treatment ( P < 0.014; n = 57 and 35, respectively). Furthermore, we found that none of the four nucleotide levels showed significant differences in SLE case–control association tests ( P > 0.2; 13 patients with SLE and the 181 shared controls) and psoriatic arthritis (PsA) case–control association tests ( P > 0.11; 42 patients with PsA and 38 healthy controls), indicating disease specificity in RA. In conclusion, our large-scale metabolome analysis demonstrated the increased plasma nucleotide levels in RA patients, which could be used as potential clinical biomarkers of RA, especially for seronegative RA. Abstract : Plasma nucleotide levels are new biomarkers for RA